Analysis of epidemiological characteristics of extrapulmonary tuberculosis from South-Central China - Yu, Yanyan; Xiang, Yu; Liu, Haican; Yang, Shuliu; Li, Machao; Liu, Binbin; Xu, Da; Wu, Yaning; Li, Wenbin; Fang, Tanwei; Li, Jixiang; Xu, Donglei; et al. (Frontiers in Public Health, 2024)
Objectives: To investigate the epidemiological and drug resistance (DR) characteristics of extrapulmonary tuberculosis (EPTB) from South-central China. Methods: EPTB inpatients with Mycobacterium tuberculosis culture positive were retrospective included at a provincial TB hospital in Hunan, a province located in South-central China from January 2013 through December 2021. Demographic, clinical and drug susceptibility data were retrieved from TB treatment records. Descriptive statistical methods and Chi-square test were used to analyzed the epidemiological and DR characteristics of EPTB. Logistic regression model was used to explore the risk factors of rifampicin (RFP) resistant/ multi-drug resistant (RR/MDR)-EPTB.Results: A total of 1324 cases were included. The EPTB patients were majorly aged 20-29 years, males (male: female ratio: 2.03) and farmers (65.63%). The most EPTB cases were found in 2013 and 2017 during the period 2013-2021. The most prevalent subtypes of EPTB were lymphatic TB (29.83%, 395/1324), followed by multiple EPTB (20.85%, 276/1324) and musculoskeletal TB (14.65%, 194/1324). Musculoskeletal TB and genitourinary TB were more inclined to act as exclusively EPTB, whilst lymphatic TB and pharyngeal/laryngeal TB were more inclined to concurrent with PTB. The drug susceptibility testing results showed that the total DR (resistant to any of RFP, isoniazid [INH], streptomycin [STR], and ethambutol [EMB]) and RR/MDR rates of EPTB were 25.23% and 12.39%, respectively. Musculoskeletal TB owned the highest rates of total DR (31.40%), INH resistance (28.90%), STR resistance (20.10%), EMB resistance (6.20%), MDR (13.90%) and Poly-DR (6.70%). Multivariable logistic regression model showed that patients aged between 20 to 59 years old (compared to 10~ years old), workers (compared to retirees), and EPTB patients from the south and west of Huan (compared to those from east of Hunan) were at risk developing RR/MDR (all OR values > 1).Our study disclosed the epidemiological and DR characteristics of EPTB in Hunan Province, China, the high DR rate among EPTB (especially musculoskeletal TB) cases highlights the needs for timely diagnosis and drug susceptibility testing tools, and the formulation of more effective regimens for EPTB especially musculoskeletal TB treatments.